Die Siphonapteren-Sammlung des DEI. (Einschließlich Katalog der in ihr enthaltenen Typen). - Kutzscher, Christian (Contributions to Entomology = Beiträge zur Entomologie, 1991)
The paper presents a catalogue of Siphonapteratypes preserved in the collections of DEI. A short introduction about the history and the actual situation of the Siphonaptera-collection is given.